ПЕДАГОГ МАГИСТРЛАРНИ ИЖОДИЙ ФАОЛИЯТГА МЕТОДОЛОГИК ТАЙЁРЛАШ САМАРАДОРЛИГИНИ ОШИРИШ - Чариев, И. (SCIENCE and SOCIETY, 2023)
The article describes ways to improve the effectiveness of methodological training of pedagogic masters for creative activity, formation of methodological training for pedagogic masters based on creative activity preparation. Their readiness to carry out pedagogical activities is related to their knowledge, skills and qualifications, and through their acquired professional competences, they provide solutions to the problems of pedagogic masters that have arisen in the educational process.